2004
DOI: 10.1124/jpet.104.067959
|View full text |Cite
|
Sign up to set email alerts
|

XP13512 [(±)-1-([(α-Isobutanoyloxyethoxy)carbonyl] aminomethyl)-1-cyclohexane Acetic Acid], A Novel Gabapentin Prodrug: II. Improved Oral Bioavailability, Dose Proportionality, and Colonic Absorption Compared with Gabapentin in Rats and Monkeys

Abstract: The absorption of gabapentin (Neurontin) is dose-dependent and variable between patients. Rapid clearance of the drug necessitates dosing three or more times per day to maintain therapeutic levels. These deficiencies appear to result from the low capacity, limited intestinal distribution, and variable expression of the solute transporter responsible for gabapentin absorption. Saturation of this transporter at doses used clinically leads to unpredictable drug exposure and potentially ineffective therapy in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…The purpose of the current work was to evaluate in vitro the metabolism and transport properties of XP13512 in comparison with gabapentin. A companion manuscript describes the effect of the superior transport properties of XP13512 on the resulting oral bioavailability, dose proportionality, colonic absorption, and tissue distribution of gabapentin in preclinical species (Cundy et al, 2004). 14 C]-gabapentin (162 mCi/mmol) was from PerkinElmer Life and Analytical Sciences (Boston, MA).…”
Section: Gabapentin (mentioning
confidence: 99%
“…The purpose of the current work was to evaluate in vitro the metabolism and transport properties of XP13512 in comparison with gabapentin. A companion manuscript describes the effect of the superior transport properties of XP13512 on the resulting oral bioavailability, dose proportionality, colonic absorption, and tissue distribution of gabapentin in preclinical species (Cundy et al, 2004). 14 C]-gabapentin (162 mCi/mmol) was from PerkinElmer Life and Analytical Sciences (Boston, MA).…”
Section: Gabapentin (mentioning
confidence: 99%
“…(Comprehensive review of the development of drug-like ligands for a 2 d.) The prodrug XP13512 (compound 25, Figure 8) has been shown to improve exposure in two different species compared to dosing gabapentin itself. XP13512 has been demonstrated to increase plasma levels of gabapentin by 9-fold in the monkey and by 17-fold in the rat following oral administration, and 34-fold in the monkey following direct intracolonic administration compared to gabapentin by the same route (Cundy et al, 2004). Compound 26 (Figure 8) is an example of a compound with a tetrazole as a carboxylic acid bioisostere, which was shown to have potent binding to a 2 d and demonstrated robust anticonvulsant activity in vivo.…”
Section: Voltage-gated Ion Channels: Novel Approaches To Modulation Omentioning
confidence: 99%
“…17 GEn delivers predictable and sustained gabapentin exposure (bioavailability ≥ 68% based on urinary recovery of gabapentin in healthy adults) compared with mgequivalent doses of gabapentin. 16,18,19 In a 12-week, placebo-controlled study, subjects with moderate-to-severe primary RLS reported significantly improved RLS symptoms with GEn 1200 mg compared with placebo. 20 A shorter 2-week study demonstrated significant treatment benefit in subjects with primary RLS with GEn 1200 mg compared with placebo, but not with GEn 600 mg. 21 The present study evaluated the efficacy and tolerability of GEn 1200 mg and 600 mg compared with placebo in subjects with moderate-tosevere primary RLS, to confirm the previous findings for GEn 1200 mg and to further evaluate whether 12-week exposure to GEn 600 mg provided significant treatment benefits.…”
Section: Efficacy Assessmentsmentioning
confidence: 99%
“…13,15 Gabapentin enacarbil (GEn) is an actively transported prodrug of gabapentin that overcomes the pharmacokinetic limitations of gabapentin through absorption by high-capacity nutrient transporters located throughout the large and small intestine. 16,17 After absorption, GEn is rapidly converted to gabapentin by non-specific carboxylesterases, primarily in intestinal epithelial cells. 17 GEn delivers predictable and sustained gabapentin exposure (bioavailability ≥ 68% based on urinary recovery of gabapentin in healthy adults) compared with mgequivalent doses of gabapentin.…”
Section: Efficacy Assessmentsmentioning
confidence: 99%